2019
DOI: 10.1177/2324709619893197
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pancreatitis Complicated by Stress Cardiomyopathy With Persistent Apical Akinesis: A Case Report and Literature Review

Abstract: Takotsubo cardiomyopathy or stress cardiomyopathy is a transient reversible cardiomyopathy characterized by regional wall motion abnormalities that usually extend beyond a single epicardial vascular distribution. It is often precipitated by acute physical or emotional stressors. In this article, we present the case of a postmenopausal woman who was admitted for management of acute pancreatitis. On the second day of admission, she developed shortness of breath and electrocardiographic abnormalities. A transthor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Acute pancreatitis not only induces a systematic inflammation response, but also is a significant physical stressor which triggers the release of catecholamines. This, in turn, can either have a direct toxic effect on the cardiac myocytes, or lead to an indirect damage by causing multivessel spasm in predisposed individuals [7]. It has been proposed that regional differences in catecholamine-induced vasocontraction, innervation, and adrenergic sensitivity might be the cause of the mechanism of the regional difference in contractility [8].…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis not only induces a systematic inflammation response, but also is a significant physical stressor which triggers the release of catecholamines. This, in turn, can either have a direct toxic effect on the cardiac myocytes, or lead to an indirect damage by causing multivessel spasm in predisposed individuals [7]. It has been proposed that regional differences in catecholamine-induced vasocontraction, innervation, and adrenergic sensitivity might be the cause of the mechanism of the regional difference in contractility [8].…”
Section: Discussionmentioning
confidence: 99%
“…All patients, where treatments were described, were discharged on a beta-blocker and ACEi, and in those whose follow-up was reported, all but one had recovered left ventricular function, ranging from as early as 10 days up to 6 weeks. Abe et al [ 4 ] reported the case of persistently reduced left ventricular function even at 4 months, which was hypothesised to be due to ongoing alcohol use (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%